The Impact Of Green Human Resource Management to Environmental Performance - Nelson, Alden; Junaidi, Junaidi; Sentoso, Anthony (Penerbit Goodwood, 2025)
Purpose: This study examines how companies’ environmental performance is affected by Green Human Resource Management (GHRM), with a focus on the moderating influence of corporate environmental ethics and the mediating effect of green organizational culture. Methodology/approach: A quantitative research approach was employed, with data acquired through surveys aimed at organizations implementing GHRM policies. The links between GHRM, green organizational culture, corporate environmental ethics, and environmental performance were examined using path analysis. Results/findings: Green organizational culture serves as a mediator between GHRM and environmental performance, and GHRM activities greatly improve corporate environmental performance. The positive correlation between GHRM and environmental performance is reinforced by corporate environmental ethics, underscoring the significance of ethical commitment in maximizing GHRM's advantages of GHRM. Conclusions: Green organizational culture and environmental ethics are key to improving sustainability, while GHRM supports but does not directly drive performance. Companies should focus on building strong green values and ethical practices. GHRM, green culture, ethics, and performance are interconnected, with ethics moderating GHRM’s impact of GHRM. To enhance GHRM’s effectiveness of GHRM, firms should offer training, promote eco-values, and align policies with sustainability goals. Limitations: As the data are restricted to companies that have implemented GHRM policies, the conclusions might not qualify as relevant to other companies. Deeper qualitative insights are not offered by quantitative methods. Contribution: This study adds to the body of knowledge in GHRM by highlighting the vital roles that environmental ethics and green organizational culture play in improving corporate environmental performance.